The Development of an Al-Muthala’ah Teaching Book for Sixth-Grade Students at Kulliyyatul Mu‘allimin Al-Islamiyyah Darussalam Gontor - Alsadika Ziaul Haq; Arih Inas Atiqahwati; Tri Wi Farma (LISANIA: Journal of Arabic Education and Literature, 2025)
This study aims to develop a textbook for Muthala‘ah al-Qirā’ah al-Wāfiyah for sixth-grade students of Kulliyyatul Mu‘allimin al-Islamiyyah (KMI), Darussalam Gontor, based on image-based media. The textbook was designed to fulfill the learning objectives established by the Quality Assurance Department and to meet the standards of the KMI curriculum. Based on initial observations, it was found that students had difficulty understanding the existing textbooks due to the lack of media integration. In addition, several errors in sentence construction were identified in the texts, which led to misunderstandings of the intended meanings. This study employed the developmental model proposed by Jerold E. Kemp. The model is circular in nature and illustrates a continuous process in implementing instructional design to create learning that is effective, efficient, and engaging. The results of this study indicate that the Muthala‘ah al-Qirā’ah al-Wāfiyah textbook is suitable for use in teaching sixth-grade students at KMI Pondok Modern Gontor. This is supported by validation results showing that the Arabic language expert awarded a score of 95.45% (in the very good category), the learning media expert awarded 92.50% (in the very good category), and the instructional design expert awarded an average score of 99% (in the very good category). The developed textbook can assist and facilitate sixth-grade students in understanding the learning materials and increase their interest in learning, particularly in muthala‘ah lessons.